Punching shear strength of reinforced concrete slabs without shear reinforcement - Jin, Ling (2011)
Reinforced concrete flat plate structure is an economical choice for residential buildings because of its simple construction processes, lower storey height and maximum architectural freedom in design. However, this kind of structure is prone to fail around the column due to concentric loading around the slab-column connection or unbalanced moment caused by unsymmetrical loading. Thus, special attention should be paid when design punching shear capacity. From literature, punching shear capacity could be predicted by various methods including the different code methods, mechanical models, plastic theory and compression field theory. For mechanical models, previous works were mainly on predicting ultimate punching shear strength of slab supported on circular column.